An alternative adhesive based technique of raising the occlusal vertical dimension - Aditi Nanda; Veena Jain; Karan Manak; Mahesh Verma (Wolters Kluwer Medknow Publications, 2014)
Purpose: Decimated dentitions may require raising the vertical dimension in some conditions while performing a full mouth rehabilitation treatment. Increase in a vertical dimension should be diagnosed by reversible methods prior to performing any irreversible methods for a minimum time period. Reversible methods like splints and overlay dentures are often used for this purpose. These methods however cannot be used in some conditions like in cases of brittle teeth. Method: An alternative technique based on adhesive technology has been described which is reversible and yet minimally traumatic to teeth. Conclusions: The technique has two basic aims. The first is to accurately implement the occlusal scheme as planned in the diagnostic wax-up in the reversible method of altering the vertical dimension. The second aim is to increase the vertical dimension with minimal damage to the teeth.